PENGARUH PENERAPAN METODE STRATAGEM MELALUI PEMBELAJARAN KOOPERATIF TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA KELAS VIII SMP NEGERI 20 PADANG - YUNITA S.Si, ALFI (Jurnal Pelangi : Research of Education and Development, 2011)
Mathematical abilities of eighth grade students at SMP N 20 Padang hadnot been satisfactory yet because the students still had difficulties inunderstanding the mathematical communication abilities. These were due theinstructional methods used were less variable and less appropriate, as an effort toovercome the above problem, the researcher used stratagem method throughcooperative learning method. The purpose of this research was to determine:whether the communication mathematical abilities of students taught by stratagemthrough cooperative learning methods were better than conventional method. Theresearch was carried out to eighth grade students at SMP N 20 Padang. Themethod used was quasi experiment with posttest only control design. The result ofdata analysis showed that: abilities mathematical communication of studentstaught by using stratagem through cooperative learning method were better thanthose through conventional method. From the above result, it can be concludedthat the use of stratagem through cooperative learning method in teachingmathematics at SMP N 20 Padang was quite effective for improving student’smathematics learning outcomes on the ability in understanding thecommunication mathematical abilities.